2017
DOI: 10.2751/jcac.18.124
|View full text |Cite
|
Sign up to set email alerts
|

Small Random Forest Models for Effective Chemogenomic Active Learning

Abstract: The identification of new compound-protein interactions has long been the fundamental quest in the field of medicinal chemistry. With increasing amounts of biochemical data, advanced machine learning techniques such as active learning have been proven to be beneficial for building high-performance prediction models upon subsets of such complex data. In a recently published paper, chemogenomic active learning had been applied to the interaction spaces of kinases and G protein-coupled receptors featuring over 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
(94 reference statements)
1
15
0
Order By: Relevance
“…These emerging methods are collectively known as chemogenomic active learning. Rakers, Reker, and Brown further demonstrated that model complexity built on qHTS data could be reduced by more than half of existing estimates.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…These emerging methods are collectively known as chemogenomic active learning. Rakers, Reker, and Brown further demonstrated that model complexity built on qHTS data could be reduced by more than half of existing estimates.…”
Section: Introductionsupporting
confidence: 90%
“…The subsequent CGAL model development is based on a collection of decision trees known as a random forest that are actively trained using a specified number of iterations or data samples. Based on previous analyses of the tradeoff between the number of trees and resulting performance, the number of trees used here was fixed at 100 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational experiments may consider the philosophy discussed herein to perform repeated executions of a model‐predict experiment such that less than half of the data per class is subsampled for model selection with the majority remainder used for prediction. Recent modeling methods have shown that often only a fraction of a dataset is sufficient to build a predictive model ,,. As in the prior studies, if distribution of prediction performances can be shown to be normally distributed by the Kolmogorov‐Smirnov test, we can consider using such a fact to forecast the chances of success in a true prospective experiment.…”
Section: Conclusion and Future Outlookmentioning
confidence: 98%